ANALISIS KESULITAN ANAK-ANAK DENGAN SINDROM DOWN DALAM MENYELESAIKAN SOAL MENULIS AWAL DI SEKOLAH KHUSUS - Septiani, Shintia Putri; Ramadhani, Amelia Nur; Ruby, Arcivid Chorynia (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze the level of difficulty and development of early writing skills in children with Down Syndrome at SLB Negeri X Kudus. The approach used is quantitative descriptive with a single subject, namely an elementary school student with intellectual disabilities due to Down Syndrome. Data collection techniques were carried out through structured observations during six meetings, documentation of student work results, and assessments using a scale of 1–5 on five main indicators, namely the ability to recognize letters, connect letters with sounds, copy writing, writing forms, and independence. Data were analyzed statistically using SPSS software through descriptive statistical tests and paired sample t-tests. The results showed a significant increase in students' writing skills, from a total score of 8 at the first meeting to 20 at the sixth meeting. The t-test showed a significance value of 0.000, which indicated that the difference was statistically significant. This increase was influenced by the use of visual media such as images and videos, a gradual approach (task analysis), and consistent positive reinforcement from the teacher. This study concludes that an adaptive, visual, and responsive learning approach to students' emotional needs is effective in developing early literacy skills in children with Down Syndrome.